A mixed grape and blueberry extract is safe for dogs to consume. Issue 1 (December 2016) - Martineau, Anne-Sophie; Leray, Véronique; Lepoudere, Anne; Blanchard, Géraldine; Bensalem, Julien; Gaudout, David; Ouguerram, Khadija; Nguyen, Patrick
Abstract Background Grape and blueberry extracts are known to protect against age-related cognitive decline. However, beneficial effects achieved by mixing grape and blueberry extracts have yet to be evaluated in dogs, or their bioavailability assessed. Of concern to us were cases of acute renal failure in dogs, after their ingestion of grapes or raisins. The European Pet Food Industry Federation (2013) considers only the grape or raisin itself to be potentially dangerous; grape-seed extractsper-se, are not considered to be a threat. Our aim was therefore to evaluate the renal and hepatic safety, and measure plasma derivatives of a polyphenol-rich extract from grape and blueberry (PEGB; from the Neurophenols Consortium) in dogs. Polyphenol expression was analyzed by UHPLC-MS/MS over 8 hours, for dogs given PEGB at 4 mg/kg. Safety was evaluated using four groups of 6 dogs. These groups received capsules containing no PEGB (control), or PEGB at 4, 20, or 40 mg/kg BW/d, for 24 weeks. Blood and urine samples were taken the week prior to study commencement, then at the end of the 24-wk study period. Routine markers of renal and liver damage, including creatinine (Creat), blood urea nitrogen, albumin, minerals, alkaline phosphatase (ALP), and alanine transaminase (ALT) were measured. Biomarkers for early renal damage were also evaluated in plasma (cystatin C (CysC), and neutrophil gelatinase-associated lipocalin (NGAL)), and urine (CysC, clusterin (Clu), and NGAL). Ratios of urinary biomarkers to Creat were calculated, and compared with acceptable maximal values obtained for healthy dogs, as reported in the literature. Results While several PEGB-specific polyphenols and metabolites were detected in dog plasma, at the end of the PEGB consumption period, our biomarker analyses presented no evidence of either renal or liver damage (Creat, BUN, ionogram, albumin and ALT, ALP). Similarly, no indication of early renal damage could be detected. Plasma CysC, urinary CysC/Creat, Clu/Creat, and NGAL/Creat ratios were all beneath reported benchmarked maximums, with no evidence of PEGB toxicity. Conclusions Long-term consumption of a pet specific blend of a polyphenol-rich extract from grape and blueberry (PEGB; from the Neurophenols Consortium), was not associated with renal or hepatic injury, and can therefore be considered safe.